Liquidity Risk Management on Financial Performance of Commercial Banks in Kenya - Oganda, Aloys Jared; Mogwambo, Vitalis Abuga; Otieno, Simeyo (International Journal of Recent Research in Commerce Economics and Management (IJRRCEM, 2020)
The banking sector in Kenya has experienced liquidity challenges ranging from funding to market risks. This research focused on the effects of asset management and deposit management on performance of commercial banks in Kenya. The specific objectives were; to establish the effect of customer deposits and asset base on performance of commercial banks in Kenya. Shiftability theory and Modern portfolio theories were used. Correlational research design with a comparative analysis approach was adopted. The target population was two commercial banks and document analysis guide was used to gather quantitative data from the banks financial statements through 2007 to 2016. The study found that deposits had a negative and significant effect on performance of both banks while asset base had a positive relationship. The study therefore recommends commercial banks to be aggressive in identifying viable ways to invest the customers’ deposits to generate income and management of commercial banks should improve the volume and value of assets at its disposal by looking for means to acquire additional assets since assets generate revenues to the commercial banks
Keywords: Banking sector; Liquidity challenges; Market risks; Commercial banks